Exploring the Beauty of the Banjarmasin River through 3D Animation as a Visual Tourism Media - Nisa, Zapiratun; Adriani, Adella; Pepriyani, Nor Lintang; Sabrila, Trifebi Shina (LPPM Universitas Sari Mulia, 2025)
The city of Banjarmasin is known as the